DR Effect of employee Dependency Ratio on Economic Growth in North Luwu District - Nurhuda, Nurhuda; Sari, Idha; Syukri, Muhammad; muddin, Hendra (CV. Kalimasada Group, 2023)
This study aims to determine the effect of employment and Dependency Ratio on economic growth in North Luwu Regency. The research method used is a quantitative method using secondary data from North Luwu Regency 2011-2020. The data collection method in the study was carried out through an online search on the BPS North Luwu page. From the results of the data process, it shows that simultaneously the variables of employment and Dependency Ratio have a positive and significant effect on economic growth in North Luwu Regency, partially the variables of employment have a positive and significant effect on economic growth and the dependency ratio variable partially has a positive and significant effect on economic growth in North Luwu Regency.